ESSESSMENT OF AVAILABLE VULNERABILITY FOR THE RESOURCES AND ENVIRONMENT IN BACH LONG VY AREA - Thanh, Tran Duc; Quan, Nguyen Van (Vietnam Journal of Marine Science and Technology, 2012)
Locating in the middle of the Gulf of Tonkin, Bach Long Vy island possesses a great potential for economic - social development and natural conservation. However, its resources and environment are strongly impacted by adverse natural factors included climate change, and human activities. Using the matrix analysis, the available vulnerability for 13 objects of resources and environment in Bach Long Vy island area was estimated generally by the impacts from 5 adverse natural factors and 10 human factors. The objects of resources and environment were classified into 4 groups distinguished by vulnerable levels. The group of  very high vulnerability consists of: 1- coral reef ecosystem, 2- beach ecosystem and 3- eroded coast; The group of high  vulnerability: 1- underground water, 2- fishery stocks, 3- ecosystem of tidal rocky flats, 4- water quality around the island, 5- island landscape and habitat, 6-  land resources on the island; The group of medium  vulnerability: 1- biodiversity and hard bottom ecosystem; The group of low vulnerability: 1- underwater  topography and  soft bottom ecosystem.